جهود الدكتور أحمد مطلوب في تجديد البلاغة العربية - المبارك، عبدالحسين Almubarak, Abdulhussein; الشويلي، نوال جاسم محمد (جامعة القادسية - كلية الآداب, 2013)
Arabic Rhetoric is of high status among Arabic language sciences , For the ancient Scholars were of remarkable treatment to it since it was but a brief inqurey and answer . Great efforts had been done to construct it , resulted in an obvious achievement of Abdul Qahir Al-jirjani ( 471H) .After awhile rhetoric went into stagnation , due to the works of speech and logic scientists , of them was Al- sakaki (626H), where he was a cused of being the one behind the rhetoric rigidity , for his works led to sold definitions and structures . He is being followed by groups of ancient and modem scholars . \ Many calls , in modern time , to renew the Arabic rhetoric , are made to get rid of the rigidity and stagnation . Many attempts are still on going to filful this task of these efforts , is Dr .Ahmad Matloob works , who has endeavored in this field for decades this research , Ahmad Matloob's efforts to renew Arabic rhetoric: presentation and evolution , aims to highlight this efforts , to show his contribution in Arabic rhetoric renewal , getting rid of stagnation ,and to present the ideas he coined . The research is of introduction ,presentation of Arabic rhetoric problems , presentation of Dr. Matloob ideas, with critiques and evolution . then the research main results , with list of references .
Keywords: اللغة العربية -- البلاغة العربية -- علماء اللغة العربية -- مطلوب ، أحمد